2021
DOI: 10.5935/1980-6906/eptpc1913993
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Brazilian’s mental health: Risk factors and related symptoms

Abstract: No momento em que escrevo este editorial, o Brasil (e o mundo) atravessam um doloroso ressurgimento da Covid-19. Não refeitos dos seus múltiplos impactos negativos -especialmente em termos de saúde mental -, somos novamente chama-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…A previous study in Vietnam found COVID-19-like symptoms linked to mental health problems (Nguyen et al, 2020). Female respondents without NCDs were at a higher risk of having CMD, which was consistent with a Brazilian study that indicated a higher risk for women (Giordani et al, 2021;Rakhamanov & Dane, 2020). It has been suggested that the higher incidence of depression among women is due to various factors.…”
Section: Discussionsupporting
confidence: 86%
“…A previous study in Vietnam found COVID-19-like symptoms linked to mental health problems (Nguyen et al, 2020). Female respondents without NCDs were at a higher risk of having CMD, which was consistent with a Brazilian study that indicated a higher risk for women (Giordani et al, 2021;Rakhamanov & Dane, 2020). It has been suggested that the higher incidence of depression among women is due to various factors.…”
Section: Discussionsupporting
confidence: 86%
“…O risco de contaminação pela COVID-19 revelou implicações psicológicas nas pessoas, contribuindo para o aumento dos níveis de estresse e ansiedade experienciados pela população durante a pandemia Carvalho, Moreira, Oliveira, Landim & Rolim Neto, 2020;Faro et al, 2020;). Ademais, as medidas de contenção do vírus e de distanciamento social se mostraram, também, fatores de risco para a saúde mental da população (Cruz et al, 2020;Enumo, Weide, Vicentini, Araujo, & Machado, 2020;Faro et al, 2020;Giordani et al, 2021;Gonçalves, Freires, Tavares, Vilar, & Gouveia, 2021;Zanon, Dellazzana-Zanon, Wechsler, Fabretti, & Rocha, 2020; visto que elevados níveis de estresse e ansiedade estão ligados às vivências do novo cotidiano pandêmico, na medida em que aparecem na forma de indicadores de ordem física, emocional, comportamental e cognitiva (Enumo et al, 2020;Maia & Dias, 2020;Wang et al, 2020;Weide, Vicentini, Araújo, Machado, & Enumo, 2020). A psicologia positiva aparece como alternativa a esses indicadores de mal-estar psicológico, propondo outras formas de lidar com os estressores do cotidiano pandêmico, resiliência e suporte social aparecem como estratégias para lidar com os estressores desse novo momento (Weide et al, 2020) Segundo Taylor et al (2020), o contexto da pandemia da COVID-19 foi propiciador da criação de medidas de mensuração de construtos psicológicos relacionados à doença, tais como medo, ansiedade, estresse e outros fenômenos psicológicos que são gerados por esse novo contexto.…”
unclassified